Innovation of Business Management Model Based on Big Data. Issue 2 (April 2021) - Zhang, Linqiang
Abstract: With the development of network technology and the advent of data and information era, China's business administration in the face of modern increasingly complex diversification of market subjects and market order is increasingly complex, it needs to require the industry and commerce departments in the performance of functions, service market subjects and other aspects to make unremitting efforts. Today, with the rapid development of Internet economy, the business administration mode is studied based on big data technology. The working mode and mode of the business administration department are analyzed through data statistics and investigation, and the current situation and problems of the service of the business administration department are analyzed and summarized and prospected.